Magnetic and Low Temperature Conductivity Studies in Oxidized Nano Ni Films - P.J. Sadashivaiah; T. Sankarappa; T. Sujatha; P. Saravanan; Santoshkumar; M. Prashantkumar; G.B. Devidas; B. Vijayakumar; N. Nagaraja; N. Sharanabasava (Журнал нано- та електронної фізики)
A set of single layered nanostructured Ni films of thickness, t = 25 nm, 50 nm, 75 nm and 100 nm have been deposited using electron beam gun evaporation technique at 473 K under high vacuum condition. From the grazing incidence X-ray diffraction (GIXRD) studies, NiO phase formation has been noted. Grain sizes of the films were determined. The microstructure was examined by scanning electron microscope (SEM) studies. Average surface roughness was determined by atomic force microscope (AFM). The room temperature magnetization has been measured using the vibrating sample magnetometer (VSM). The coercive field was observed to be increasing with increasing t and became maximum for t = 75 nm and decreases for further increase in t. The behavior of coercive field with t indicated softness of the films. Low temperature electrical conductivity in the range from 5 K to 300 K has been measured. Temperature dependence of electrical conductivity showed semiconducting behavior. At temperatures above θD/2 (θD is the Debye temperature), the conductivity behavior has been understood in the light of Mott’s small polaron hopping model and activation energies were determined. An attempt has been made to understand conductivity variation below θD/2 using variable range hopping models due to Mott and Greaves.